Atlas fracture after electroconvulsive therapy - Murtaza Rashid; Majed Aljohani; Bandar Al Mufareh; Omar Alkharraz (Journal of Spine Practice)
Background: Since the first-time electroconvulsive therapy was performed in 1938, it remains to this day as one of the most effective forms of treatment for patients with major depression and other psychiatric conditions. It works by a controlled electric current passed through the scalp and selected parts of the brain to induce a grand mal seizure. Due to its mechanism of action, the possibility of developing a physical trauma although rare, especially if done under an adequate modified form, is still possible.